KAJIAN FAKTOR LINGKUNGAN HUNIAN TERHADAP KEJADIAN TUBERKULOSIS DI KECAMATAN BOJONGLOA KIDUL, BANDUNG - Faulinasari Karmaputeri, Aldia
Tuberculosis is an infectious disease that has infected almost a third of the world's population. Indonesia itself was ranked as the fourth country with the highest number of tuberculosis patients. Subdistrict of Bojongloa Kidul is one area in Bandung with pretty high number of tuberculosis patients. One factor that plays a role in the spread of tuberculosis bacteria is environmental sanitation. This study aimed to compare the environmental factors i.e. lighting, humidity, ACH, ventilation, and residential density with the standards and to determine the influence of each of these factors to the incidence of tuberculosis in a shelter. This study is an observational study with a type of case-control study. The number of samples in this study was 60 respondents consisting of 30 cases and 30 controls. Data collection was conducted in the Subdistrict of Bojongloa Kidul Bandung consists of measuring environmental factors, interviews, and observation. The data were analyzed by chi square test, calculating odds ratios, and multiple regression linear analysis. The result showed only residential density factor that was statistically significant, while other factors were not.Odds ratio (OR) value of lighting was 2.786, humidity 1.75, ACH 1.643, ventilation 2.615, and residential density 3.143. Correlation coefficient of environmental factor that did not meet the standard with tuberculosis case was 0.202 for lighting, 0.136 for humidity factor, 0.111 for ACH, 0.235 for ventilation, and 0.272 for residential density factor. Correlation coefficients that were closer to 0 instead of 1 indicated that all the environmental factors studied had weak relationships with tuberculosis case. The regression equation obtained was y (tuberculosis case) = 0,04 + 0,173 (lighting) + 0,208 (humidity) – 0,007 (ACH) + 0,282 (ventilation area) + 0,22 (residential density).